Effect of Orgalife Fertilizer on Some Quality Properties of the Seed and Growth Potential of Two Rice Varieties (Oryza sativa L.) Cultivated in North Macedonia - Spaseva, Brankica; Mitrushev, Ivo; Andreevska, Danica; Andov, Dobre; Simeonovska, Emilija; Gjosheva Kovachevikj, Marija (Trakya University, Edirne, Turkey, 2021)
The aim of this study was to examine the effect of Orgalife (liquid organic microbial fertilizer based on manure from californian earthworms) on the seeds of two rice varieties, San Andrea and Opale, obtained from three production years: 2018, 2019 and 2020. They were treated with three different concentrations (3.3%, 6.7% and 9.9%) compared to control (distilled water). Germination energy, total seed germination, germination index, seedlings growth (root length, shoot length, dry seedling weight) and vigor index (I and II) were examined. One-way analysis of variance (ANOVA) was carried out and separation of means was performed using the LSD test at P=0.05 and P=0.01 significance level. The values of all treatments for all parameters were compared with the control. Germination energy and total germination for Opale in 2020 showed statistical significance for the 3.3% concentration at P=0.05, while for San Andrea the same significance was noticed only for the germination energy. Germination index for Opale gave statistically significant results only for the 2020 production year at P=0.05. For San Andrea the situation is slightly different where the treatments affected the germination index only for 2018 and 2020. Orgalife treatments increased the vigor index I and II in 2020 for both varieties and for both levels of significance. The length of the seedlings for Opale in 2020 was positively affected by the 3.3% concentration in both levels of significance, while San Andrea in the same year had statistical significance for the 9.9% concentration only for P=0.05. The results for the dry matter showed statistical significance for San Andrea for the 6.7% concentration in 2018. As an overall conclusion, we can say that the use of the Orgalife fertilizer showed to be reasonable for the seedling growth and development, better than the effect on the germination parameters.
/
Keywords: organic fertilizer Orgalife, rice seed, growth promotion, germination energy, total germination and seedling growth